PETER DOIG’S ART AS A SIGNIFICATION OF THE RE-APPEARANCE OF THE SUBLIME IN CONTEMPORARY BRITISH LANDSCAPE PAINTING - Tzanetoulakou, Eftychia (Design/Arts/Culture, 2023)
Purpose: The core of this research is the multi-layered and diverse presence of the Sublime in art today, as analysed through the oeuvre of Peter Doig, the contemporary British painter who belongs to the stream of the Young British Artists, which was developed in Great Britain in the 1990s. Topic: The present research begins with the definition of the idea of the Sublime and continues with a historical review of its manifestations in British art. Peter Doig is chosen because it is a suitable field of research into the current image of the Sublime. Methodology: Peter Doig’s work will be thoroughly examined so that the above view can be demonstrated, through a critical analysis of his paintings, and the similarities and differences with the powerful landscape painting of the 19th-century Romanticism that filled the viewer with awe and fear. Doig translates this artistic knowledge into a peculiar, internally experienced image-making that acrobats on the fringes of the established structures of artistic composition, attempting to portray the unpresentable, the timeless, the transcendent, the ambiguous, the illusory, the after-human elements that construct the landscape of Today. The selected works’ analysis is based on the immediacy of representation as an independent carrier of energy of human experience, which leads the artist to re-use the medium of painting. The research continues by examining, through its painting techniques but also via his use of photography and ready-made postcards, the ways in which the artist uses the materiality of the medium to test how the seemingly closed boundaries of representation expand into many fields of feeling, reading and understanding a timeless Now. Result: The research concludes with critical predictions about the directions and the position that the notion of the Sublime may take, starting from the creative codes in the work of Peter Doig. The paper does not seek to build a position based on unshakable, definitive and non-negotiable conclusions, but to constitute an original and thorough academic springboard, with poetic coordinates of aesthetic consideration, in the research on the applications of the painterly Sublime today.